OPLS Force Field for Choline Chloride-Based Deep Eutectic Solvents - Doherty, Brian; Acevedo, Orlando (The journal of physical chemistry. B, 2018)
Deep eutectic solvents (DES) are a class of solvents frequently composed of choline chloride and a neutral hydrogen bond donor (HBD) at ratios of 1:1, 1:2, or 1:3, respectively. As cost-effective and eco-friendly solvents, DESs have gained considerable popularity in multiple fields, including materials, separations, and nanotechnology. In the present work, a comprehensive set of transferable parameters have been fine-tuned to accurately reproduce bulk-phase physical properties and local intermolecular interactions for 8 different choline chloride-based DESs. This nonpolarizable force field, OPLS-DES, gave near quantitative agreement at multiple temperatures for experimental densities, viscosities, heat capacities, and surface tensions yielding overall mean absolute errors (MAEs) of ca. 1.1%, 1.6%, 5.5%, and 1.5%, respectively. Local interactions and solvent structuring between the ions and HBDs, including urea, glycerol, phenol, ethylene glycol, levulinic acid, oxalic acid, and malonic acid, were accurately reproduced when compared to radial distribution functions and coordination numbers derived from experimental liquid-phase neutron diffraction data and from first-principles molecular dynamics simulations. The reproduction of transport properties presented a considerable challenge and behaved more like a supercooled liquid near room temperature; higher-temperature simulations, e.g., 400–500 K, or an alternative polarizable force field is recommended when computing self-diffusion coefficients.